Contribuições para o conhecimento dos efeitos do BHT e outros antioxidantes no fígado - Castro, Lorena dos Santos (2017)
Butylated hydroxytoluene (BHT) is amply utilized as an antioxidant in industrially processes foods, cosmetics, pharmaceutical and petrochemical products. It is also commercialized in the form of capsules as a food and health supplement. As antioxidant, BHT inhibits lipid peroxidation, an effect that it also exerts in biological systems. There is also a universal consensus that ingestion of molecular species able to scavenge free radicals (antioxidants) can, in part at least, prevent the deleterious effects of the reactive oxygen species (ROS). The mitochondrial ROS production can contribute significantly to damages to the organelles in several pathologies. For this reason, good free radical scavengers should be active at the lowest possible concentration, allowing the ingestion of lowest possible doses. The evaluation of the antioxidant activity of a given substance is usually assessed by chemical methods, such as those ones based on the capacity of scavenging free radicals generated by the compounds 2,2 -azino-bis-3-ethylbenzothiazoline-6-sulphonic acid (ABTS) and 1,1-diphenyl-2-picryl-hydrazyl (DPPH). There is obviously no guarantee that a given substance active in scavenging free radicals in an artificial system will also be able to scavenge with the same efficiency the reactive oxygen species produced in the mitochondria, for example. In addition to its effects as antioxidant, potential adverse effects of BHT were already reported. For example, there are studies showing that BHT labilizes the lisosomal membranes and disorganizes the mitochondrial structure, facts that could suggest that BHT interferes with cellular metabolism. In fact, there are reports that BHT affects mitochondrial functioning by, at least, two different mechanisms: uncoupling between electron transfer and oxidative phosphorylation and inhibition of complex I of the electron transport chain. This data suggest, in theory, that BHT should either stimulate or inhibit oxygen uptake, stimulate catabolic pathways and inhibit anabolic pathways. Such actions, beside others, have been clearly demonstrated to occur with several uncouplers and respiratory inhibitors. Taking into account what was exposed above, this work has two main objectives: 1) to conduct a systematic study on the effects of BHT on the rat liver, using both the isolated perfused rat liver and isolated mitochondria; 2) to compare the free radical scavenging activity of BHT and other well known antioxidants in chemical systems and in isolated mitochondria. Regarding the latter aspect, this study should clarify about the real antioxidant potential of BHT and several other antioxidants in a biological system (ROS generation in mitochondria). Male Wistar rats weighing 200 280 g were used in all experiments. All experiments were done in accordance with the worldwide accepted ethical guidelines for animal experimentation and were previously approved by the Ethics Committee of Animal Experimentation of the University of Maringá (protocol n. 9120290915). Isolated perfused rat liver experiments were done using hemoglobin-free, non-recirculating perfusion (Krebs/Henseleit-bicarbonate buffer, pH 7.4, saturated with O2:CO2 in the proportion of 95:5). BHT was dissolved into the perfusion fluid and infused in the concentration range of 1-500 μM. Lactate and fructose were used as gluconeogenic substrates. Samples of the perfusion fluid were collected and enzymatically analysed for glucose, lactate and pyruvate. Oxygen uptake was continuously monitored by a platinum electrode. The mitochondrial respiratory activity was evaluated by two different assays. The first one was the classical assay in which intact phosphorylating mitochondria were used. Succinate was used as the substrate and the rate of oxygen uptake in the presence (state III) or in the absence (state IV) of ADP was measured, as well as the respiratory control ratio (RC). The final BHT concentrations in this assay were in the range between 10 and 100 μM. Besides this, assays with non-phosphorylating mitochondria were also performed, with the addition of oligomycin (a classical inhibitor of ATP synthase). Succinate was also used as the substrate and BHT was tested in the range between 2x10-9 to 10-4 M. The effects of BHT and 13 other antioxidants on ROS production in mitochondria were also investigated. The rate of mitochondrial ROS production was estimated by measuring the linear fluorescence increase (504 nm for excitation and 529 nm for emission) due to 2 -7 -dichlorofluorescein (DCF) formation from the reduced form of 2 -7 -dichlorofluorescein (DCFH) via oxidation by H2O2 in the presence of horseradish peroxidase, using succinate as substrate. Finally, the in vitro chemical antioxidant capacities were evaluated using both the 2,2 -azino-bis-3-ethylbenzothiazoline-6-sulphonic acid (ABTS) and the 1,1-diphenyl-2-picryl-hydrazyl (DPPH) assays. We did not found any signs that BHT uncouples oxidative phosphorylation nor that it inhibits the respiratory chain in the perfused liver in a significant way, although these effects seem to be clear in isolated mitochondria. Contrary to what is expected from uncouplers, BHT did not significantly stimulate oxygen uptake nor had an inhibitory action on glucose synthesis from lactate. Actually, there was no inhibition of glucose synthesis or oxygen consumption in the concentration range up to 200 μM. Only at the BHT concentration of 500 μM small increments in both parameters were found. Pyruvate production presented an increasing tendency at 50 μM, followed by a peak increment at 100 μM and a subsequent return to the basal levels. Experiments were also done with very low concentrations of BHT, namely 1 μM (10-6 M), by virtue of the report that BHT might uncouple phosphorylation at very low concentrations (10-9 to 10-6 M). However, no modifications of oxygen uptake, glucose production and pyruvate production were found at low concentrations. Transformation of fructose into glucose was also not affected by BHT. Only lactate production was slightly increased at the concentration of 100 μM...